Emotions, Everyday Life and Sociology - Jacobsen, Michael Hviid (Milton : Routledge, 2018)
This volume explores the emotions that are intricately woven into the texture of everyday life and experience. A contribution to the literature on the sociology of emotions, it focuses on the role of emotions as being integral to daily life, broadening our understanding by examining both 'core' emotions and those that are often overlooked or omitted from more conventional studies. Bringing together theoretical and empirical studies from scholars across a range of subjects, including sociology, psychology, cultural studies, history, politics and cognitive science, this international collection centres on the 'everyday-ness' of emotional experience.
7. Embarrassment: Experiencing awkward self-awareness in everyday lifeIntroduction; Researching embarrassment; Embarrassment and shame -- same same but different; Embarrassment typologies -- conceptualising causes, functions and consequences; Embarrassment, role segregation and the interaction order; From 'nice guy' theories to the enjoyment of observing embarrassment; Conclusion; References; 8. Shyness: Self-consciously perceived relative social incompetence; Introduction; The shy self: subjective experiences; Performing the shy role; Managing shyness as a deviant identity; Conclusion
Description based upon print version of record.
Introduction
OCLC-licensed vendor bibliographic record.
Keywords: PSYCHOLOGY / Social Psychology; SOCIAL SCIENCE / Sociology / General